The roles of epigallocatechin-3-gallate in the treatment of neuropathic pain: an update on preclinical in vivo studies and future perspectives - Bimonte S; Cascella M; Schiavone V; Mehrabi-Kermani F; Cuomo A (Dove Medical Press, 2017)
Sabrina Bimonte,1,* Marco Cascella,1,* Vincenzo Schiavone,2 Farrokh Mehrabi-Kermani,3 Arturo Cuomo1 1Division of Anesthesia and Pain Medicine, Istituto Nazionale Tumori – IRCCS – “Fondazione G. Pascale”, Naples, Italy; 2Division of Anesthesia and Intensive Care, Hospital “Pineta Grande”, Castel Volturno, Caserta, Italy; 3Division of Neurosurgery, Hospital “Pineta Grande”, Castel Volturno, Caserta, Italy *These authors contributed equally to this work Abstract: Neuropathic pain (NP) is a complex and chronic disease caused by lesions or defects of the somatosensory nervous system. The treatments normally used for managing NP usually lack efficacy. Several animal models of NP have been engineered in order to understand the molecular mechanisms underlying NP and to find alternative molecules to use as new therapeutic agents. Preclinical in vivo studies identified the epigallocatechin-3-gallate (EGCG), a main active component of green tea (Camellia sinensis), as a possible therapeutic molecule for NP treatment due to its anti-inflammatory and antioxidant properties. Interestingly, it has been shown that EGCG reduced bone cancer pain. The purpose of this article is to discuss the potential use of EGCG for control and treatment of NP, by reviewing the preclinical studies reported in the literature and by shedding light on the potential schemes based on EGCG’s application in clinical practices. Keywords: epigallocatechin-3-gallate, EGCG, natural compound, neuropathic pain, animal models of neuropathic pain, cancer bone pain